An Investigation of the Effect of Covid-19 on Efficient Market Hypothesis (EMH) Anomalies: Econometric Approach - Widodo, Purwanto (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The research aims to analyze the influence of the Covid-19 crisis on changes in the daily return pattern of the LQ45 Index, and to see whether the daily return pattern of the LQ45 Index is efficient as argued by the EMH (Efficient Market Hypothesis). The observation period was before and during Covid 19. Data analysis used an econometric approach to test any EMH anomalies, as well as running the ARCH-GARCH model due to the use of dummy variables. The analysis results show that Covid-19 has no effect on the daily return pattern of LQ45, The Week Four effect is proven, but The Day of Week effect, Monday effect and Weekend effect are not found. Another finding that the trading day anomaly testing model is sensitive to the error term distribution, also suggests that good news or bad news in volatility not only depends on the asymmetric model but also the choice of error term distribution.